Design and Application Test of English as a Foreign Language ( TOEFL ) Prediction of Self Access Centre ( SAC ) Islamic State University Sunan Ampel Surabaya - Muhammad Risa Fahmi; Titik Lusiani; Marya Mujayana (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
UIN Sunan Ampel was established in 1950 with the name of Institut Agama Islam Negeri (IAIN) Sunan Ampel. IAIN Sunan Ampel was built on the idea of Muslim society in East Java area who want to establish college under Ministry of Religius Affairs. In the 2013 IAIN Sunan Ampel transform into Universitas Islam Negeri (UIN) Sunan Ampel. On the business process, UIN Sunan Ampel is supported by some divisions. Self Access Centre (SAC) division is one of divisions which helps business process at UIN Sunan Ampel. The principal task of SAC is to educate and to train students to master foreign languages (Arabic and English). One of the programs in SAC is Test of English as a Foreign Language (TOEFL) Prediction. There are some problems found in the TOEFL Prediction, such as; test scoring processs that takes a long time,throud in the scoring proccess, and the random system of TOEFL Prediction. From those problems, it is needed the application which helps in the test administration proccess and the implementation of the test. The steps on making the application start with communication, planning, modelling, construction, and operation. After being tested, TOEFL prediction application can handle the proccess of registration, buying ticket examination, making exercise package, inputing exercise examination, uploading file listening test, test assessment, test scoring , and printing certificate.